Role of interferons in the antiviral battle: from virus-host crosstalk to prophylactic and therapeutic potential in SARS-CoV-2 infection - Mihaescu, Grigore; Chifiriuc, Mariana Carmen; Filip, Roxana; Bleotu, Coralia; Ditu, Lia Mara; Constantin, Marian; Cristian, Roxana-Elena; Grigore, Raluca; Bertesteanu, Serban Vifor; Bertesteanu, Gloria; Vrancianu, Corneliu Ovidiu (Frontiers in Immunology, 2024)
Mammalians sense antigenic messages from infectious agents that penetrate the respiratory and digestive epithelium, as well as signals from damaged host cells through membrane and cytosolic receptors. The transduction of these signals triggers a personalized response, depending on the nature of the stimulus and the host's genetics, physiological condition, and comorbidities. Interferons (IFNs) are the primary effectors of the innate immune response, and their synthesis is activated in most cells within a few hours after pathogen invasion. IFNs are primarily synthesized in infected cells, but their anti-infective effect is extended to the neighboring cells by autocrine and paracrine action. The emergence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic in 2019 was a stark reminder of the potential threat posed by newly emerging viruses. This pandemic has also triggered an overwhelming influx of research studies aiming to unveil the mechanisms of protective versus pathogenic host immune responses induced by SARS-CoV-2. The purpose of this review is to describe the role of IFNs as vital players in the battle against SARS-CoV-2 infection. We will briefly characterize and classify IFNs, present the inductors of IFN synthesis, their sensors, and signaling pathways, and then discuss the role of IFNs in controlling the evolution of SARS-CoV-2 infection and its clinical outcome. Finally, we will present the perspectives and controversies regarding the prophylactic and therapeutic potential of IFNs in SARS-CoV-2 infection.